Collaborative Communication Preserving Sawarna Beach Ecosystem Towards Sustainable Tourism Development - Irawan, Enjang Pera; Subiakto, Vania Utamie; Erlita, Novi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Tourism is a vital sector for the national economy, but the increase in tourism at Sawarna Beach threatens the sustainability of the local ecosystem and the economy of the community. This research analyzes sustainable tourism communication to support the conservation of the Sawarna Beach ecosystem. This research uses a case study method with a qualitative approach, involving literature review, focus group discussions, interviews, observations, and qualitative data analysis. The research findings emphasize the importance of multi-stakeholder collaboration involving local governments, local communities, tourism entrepreneurs, and NGOs in conservation efforts. The success of conservation heavily relies on effective coordination and structured communication. Although multiplatform media such as websites and social media are important for raising environmental awareness, their use is still not optimal. Participatory approaches, such as beach clean-up activities, have proven effective in increasing participation and environmental awareness. This research acknowledges limitations in geographical scope as well as a lack of exploration into the potential conflicts among stakeholders. Recommendations include further research on conflict dynamics, more effective communication strategies, and more intensive management of digital media and outdoor media to enhance community engagement in environmental conservation.